Decellularization of Trachea With Combined Techniques for Tissue-Engineered Trachea Transplantation - Aysegul Batioglu-Karaaltin; Ercüment Ovali; Mehmet V Karaaltin; Murat Yener; Mehmet Yılmaz; Fatma Eyüpoğlu; Yetkin Zeki Yılmaz; Erol Rüştü Bozkurt; Necdet Demir; Esma Konuk; Ergun Süreyya Bozdağ; Özgür Yiğit; et al. (Clinical and Experimental Otorhinolaryngology, 2019)
Objectives The purpose of this study is to shorten the decellularization time of trachea by using combination of physical, chemical, and enzymatic techniques. Methods Approximately 3.5-cm-long tracheal segments from 42 New Zealand rabbits (3.5±0.5 kg) were separated into seven groups according to decellularization protocols. After decellularization, cellular regions, matrix and strength and endurance of the scaffold were followed up. Results DNA content in all groups was measured under 50 ng/mg and there was no significant difference for the glycosaminoglycan content between group 3 (lyophilization+deoxycholic acid+de-oxyribonuclease method) and control group (P=0.46). None of the decellularized groups was different than the normal trachea in tensile stress values (P>0.05). Glucose consumption and lactic acid levels measured from supernatants of all decellularized groups were close to group with cells only (76 mg/dL and 53 mg/L). Conclusion Using combination methods may reduce exposure to chemicals, prevent the excessive influence of the matrix, and shorten the decellularization time.